Spectators in canoes at the Tlingit potlatch, Klukwan, Alaska, October 12, 1898 - Hegg, Eric A., 1867-1948 (1898)
Shows Tlingit Indians in ceremonial and western dress, some holding rifles and carrying American flags. Caption on image: "Watching the dance at the Klukwan potlach Oct 12 '98"